Peran Dinas Perikanan Dalam Pemberdayaan Masyarakat Nelayan Dan Implikasinya Terhadap Ketahanan Ekonomi Keluarga Nelayan (Studi Pada Kampung Nelayan Di Kecamatan Bula, Kabupaten Seram Bagian Timur, Provinsi Maluku) - Zarita Kaulika Rumarey Wattimena; Rustadi Rustadi; Suadi Suadi (Jurnal Ketahanan Nasional, 2022)
ABSTRACT This study aimed to analyzed the role of  Department of Fishery of Seram Bagian Timur Regency  using the Siagian theory in 2003, through 5 role indicators namely the role of stabilizer, innovator, modernizr, pioneer and implementer as well as the implications of the role of the service on the economic resilience of fishermen's families which included: place of residence (home ownership) , income, education costs and health insurance in Bula Fisherman's Village SBT Regency.This research was a qualitative descriptive study, with data collection techniques using qualitative methods with samples of 6 informants from the officers in the Fisheries Services and 5 fishers informants representing 3 fish farmer groups. The data collection techniques used were (1) observation (2) interviews, and (3) documentation with data analysis techniques through qualitative description analysis which drew conclusions analytically through the stages of data reduction, data presentation and conclusion drawing.The results of the study indicated that Department of Fishery of SBT Regency had not carried out its main duties and functions optimally. The limitations of its implementation, both the role and implementation of policies, were still hampered by a number of factors, namely budget constraints, low quality of human resources, government policies and inadequate facilities and infrastructure. So, that the local governments had not been effective in managing and utilizing fishery resources. The implication of the role of Office of Fishery of SBT in empowering fishermen showed that it still had not had a positive influence on the economic condition of the fishermen's families, most of the fishing families had family economic resilience that was included in the less resilient category, namely there were still many family of fisherman who lived in poverty. In order to supporedt the success of the role of the Department of Fisheries, a number of supporting factors were needed that could encourage the regional economy through marine and fisheries-based regional development, namely fishery resources, human resources and government policies (budget).